What Follows After - Walsh, Dan 1957- (Thorndike, Maine : Center Point Large Print, 2014)
"Two brothers run away from their Florida home, head for their aunt's house in Georgia, and refuse to come home until their parents get back together. When things go terribly wrong, their parents must come to grips with years of neglect and mistrust in order to recover their beloved sons, their love for one another, and their marriage"--
Keywords: Large type books; Christian fiction